Effect of row orientation and cowpea row numbers on sweet corn-cowpea intercropping - Atikah Fajri; Heni Purnamawati; Maya Melati (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2025)
Intercropping between sweet corn (Zea mays L. var. saccharata Sturt) and cowpea (Vigna unguiculata L. Walp) can improve land productivity, but requires optimization of row orientation and cowpea row number. This study evaluated the effects of row orientation and cowpea row number on the growth, yield, and economic performance of sweet corn–cowpea intercropping. The experiment was conducted from June to September 2024 at the IPB experimental field in Sawah Baru, Bogor, Indonesia. A split-plot design with four replications was employed. The main plots consisted of two row orientations (North–South and East–West), while the sub-plots included maize monoculture, intercropping with one row, and two rows of cowpea. A significant interaction between row orientation and cowpea row number was observed on maize height, leaf number, and stem diameter at two weeks after planting. Although row orientation did not significantly affect maize and cowpea performance, the East–West orientation increased cowpea yield by 14.6% and reduced maize yield by 5.3% compared to the North–South orientation. The East–West orientation combined with one cowpea row produced the highest land equivalent ratio (LER = 1.93) and benefit–cost ratio (R/C = 1.45). Keywords: LER, R/C ratio, aggressivity, competitive ratio